Hukuman Pidana Mati bagi Pelaku Tindak Pidana Pembunuhan Berencana dalam Tafsir Ibn 'Asyur, al-Tahrir wa al-Tanwir: Pandangan Ibnu 'Asyur Tentang Tindak Pidana Pembunuhan Berencana - Nawawi, Ruston (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2023)
Considering the many controversies surrounding the death penalty, it is very important to present a discussion of the issue of the death penalty from various social justice and legal perspectives, especially the perspective of the Qur’an. This study aims to reveal ibn ‘Asyur’s Tafsir, al-Tahrir wa al-Tanwir. Within the framework of efforts to combine progressive and realist jurisprudence according to developments over time, the urgency of resolving problems that have arisen since the classical period is something that must be done if the Indonesian Muslim, especially observers of Islamic law, really wants to resolve Islamic legal problems and implement them in this country seriously. Not too many studies have been carried out intensively and seriously enough on this issue. Based on the idea that the polemic regarding this issue has not yet ended, a serious study of the death penalty from an Islamic legal perspective needs to be carried out.